Surface mycoflora in stored grains of naked oats - Voženílková Bohumila; Moudry Jan; Čermák Bohuslav (Zbornik Matice Srpske za Prirodne Nauke, 2005)
In the framework of small-site experiments we examined the biopreparation Supresivit S 2 containing the propagules of the antagonistic fungus Trichoderma harzianum. The small-site experiments, which were carried out in the experimental plot of the Department of Crop Production (University of South Bohemia in Češke Buđejovice, Faculty of Agriculture), were aimed at impairing the biotic fungistasis by biological means applied to the grains of naked oats, variety Adam. Our objective was to accomplish surface microbial analysis of stored naked oats grains, variety Adam, after the application of the biofungicide Supresivit S 2 in combination with surface treatment of the grains and biological screen applied during vegetation period. In particular variants of the experiment we estimated the values of the levels of bacteria and fungi representation in the surface parts of stored grains and analysed the contents of some mycotoxins produced by the fungi of the genus Fusarium. The highest numbers of bacteria and fungi on the surface of the investigated grains were found in the variant treated by the bioagent (Supresivit S 2) namely 82.000.000 spores of bacteria and 110.000 spores of fungi (Cladosporium, Verticillium, Coelomycetum) per 1 g of grain. Also the fungi of the genus Fusarium were most numerous in the variant oats - bioagent namely 250 spores per 1 g of grain. In all particular variants the amounts of mycotoxins were considerably below the known effective doses for animals and plants. The largest amount of vomitoxin was found in the variant chemical standard (Rovral TS, effective substance Carbendazim 17.5% and Iprodion 35%) - 18 ug. Zearalenon was found in all variants below 5 ug. Lower doses of ergosterin were found in the variant treated by the bioagent 4.7 mg/kg.